Information and Communication Technology in Language Learning - Rakhimbayevna, Rajabova Diloram; Sabokhat, Sultanbayeva; Yulduz, Otanazarova (Indonesian Journal of Education Methods Development, 2019)
This thesis deals with the possible help of technology for learners of the English language, especially for those suffering from any kind of SLD. It describes the concept of a multisensory approach together with individually preferred learning styles applied in learning the language through the use of ICT tools, related methods, and benefits, and provides several practical examples. It is focused on the level of involvement of human senses in particular interactive ICT activities available for learning the English language.